Distinct Connexin43, Connexin31, and Pannexin1 expression patterns in the cochlea of a non-human primate - Makoto Hosoya; Satoshi Suda; Masafumi Ueno; Marie N. Shimanuki; Takanori Nishiyama; Naoki Oishi; Hiroyuki Ozawa (Scientific Reports)
Abstract Membrane channels play an important role in auditory processes. Connexins and pannexins are membrane channels that exist in the cochlea. Connexin26 and connexin30 have been previously shown to be differentially expressed in the developing cochlea of primates in a species-specific manner. However, whether other connexins and pannexins are also expressed in the developing primate cochlea has not been investigated. In this study, we sought to examine the expression patterns of connexin43, connexin31, and pannexin1 during cochlear development in a primate animal model, the common marmoset, to determine the differences observed between the marmoset and existing rodent models. Our observations revealed both interspecies differences in the expression patterns of these genes and similarities between rodents and primates. These results indicate that the spatiotemporal patterns of connexin and pannexin expression are complex and differ between rodents and primates. They also highlight the importance of carefully observing differences in developmental changes in connexins and pannexins between humans and rodents.